An ATP-activated spatiotemporally controlled hydrogel prodrug system for treating multidrug-resistant bacteria-infected pressure ulcers - Xiaoliang Qi; Yajing Xiang; Ying Li; Jiajia Wang; Yuxi Chen; Yulong Lan; Jinsong Liu; Jianliang Shen (Bioactive Materials)
Adenosine triphosphate (ATP)-activated prodrug approaches demonstrate potential in antibacterial uses. However, their efficacy frequently faces obstacles due to uncontrolled premature activation and spatiotemporal distribution differences under physiological circumstances. Herein, we present an endogenous ATP-activated prodrug system (termed ISD3) consisting of nanoparticles (indole-3-acetic acid/zeolitic imidazolate framework-8@polydopamine@platinum, IZPP) embedded in a silk fibroin-based hydrogel, aimed at treating multidrug-resistant (MDR) bacteria-infected pressure ulcers. Initially, an ultraviolet-triggered adhesive ISD3 barrier is formed over the pressure ulcer wound by a simple local injection. Subsequently, the bacteria-secreted ATP prompts the degradation of IZPP, allowing the loaded IAA prodrug and nanozyme to encounter spatiotemporally on a single carrier, thereby efficiently generating reactive oxygen species (ROS). Exposure to 808 nm near-infrared light enhances the catalytic reaction speed, boosting ROS levels for stronger antibacterial action. Once optimal antibacterial action is reached, ISD3 switches to a dormant state, halting any further ROS production. Moreover, the bioactive components in ISD3 can exert anti-inflammatory functions, aiding in pressure ulcer recovery. Overall, our research introduces a hydrogel prodrug strategy activated by bacterial endogenous ATP, which precisely manages ROS generation and accelerates the recovery of MDR bacteria-infected pressure ulcers.